Washington Mt. St. Helens Quadrangle Surveyed in 1913-14 & 1916 - Pike, Albert; Mckinley, C.P.; Lewis, J.L. (Washington US Geological Survey, 1919)
Datum is mean sea level
Approximate Mean Declination, 1916
Diagram of township
Keywords: Topographic Map